Answer:
Dependent
![x=3-3z](https://img.qammunity.org/2020/formulas/mathematics/high-school/oa4f30ubdhmb00yh3jlroz4amo8noo19mz.png)
![y=-5z-1](https://img.qammunity.org/2020/formulas/mathematics/high-school/6nxxlypojzvis6tzc9gf9iszotnfegl7cc.png)
Explanation:
We are given that system of equations
(Equation I)
( Equation II)
(Equation III)
Equation III multiply by 3 and then add to equation I then we get
![-7x-21z=-21](https://img.qammunity.org/2020/formulas/mathematics/high-school/jw5yz3lyqkrn6eakz9oz8vffujiwyz9o5i.png)
Divided by -7 then we get
Now , obtained equation subtract from equation II then we get
0=0
Hence, equation II is a linear combination of equation I and equation III.
Therefore, system is dependent because system has infinite solutions.
![x=3-3z](https://img.qammunity.org/2020/formulas/mathematics/high-school/oa4f30ubdhmb00yh3jlroz4amo8noo19mz.png)
Substitute the value of x in equation I then we get
![2(3-3z)-3y-9z=9](https://img.qammunity.org/2020/formulas/mathematics/high-school/ci3ifgxmg08y9nhosuxafx60ex5lm2nuqo.png)
![6-6z-3y-9z=9](https://img.qammunity.org/2020/formulas/mathematics/high-school/ygvnryu20hasm24rurqo0xgd2vtny60wcy.png)
![3y=-15z+6-9=-15z-3](https://img.qammunity.org/2020/formulas/mathematics/high-school/in23s7sfbtasyjxr5ivy6m7lbmuc4m29w5.png)
![y=-5z-1](https://img.qammunity.org/2020/formulas/mathematics/high-school/6nxxlypojzvis6tzc9gf9iszotnfegl7cc.png)